2020
DOI: 10.1097/prs.0000000000006471
|View full text |Cite
|
Sign up to set email alerts
|

The Reducing Opioid Use in Children with Clefts Protocol: A Multidisciplinary Quality Improvement Effort to Reduce Perioperative Opioid Use in Patients Undergoing Cleft Surgery

Abstract: Background: Cleft repair requires multiple operations from infancy through adolescence, with repeated exposure to opioids and their associated risks. The authors implemented a quality improvement project to reduce perioperative opioid exposure in their cleft lip/palate population. Methods: After identifying key drivers of perioperative opioid administration, quality improvement interventions were developed to address these key drivers and reduce postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…3,4 Thus, developing effective strategies to manage perioperative pain, a key component of such protocols, remains a focus of cleft care. 5…”
mentioning
confidence: 99%
“…3,4 Thus, developing effective strategies to manage perioperative pain, a key component of such protocols, remains a focus of cleft care. 5…”
mentioning
confidence: 99%
“…Lee and colleagues advocated for decreasing morphine use after pediatric cleft surgery by strict adherence to a standardized order set and administration of intraoperative nerve blocks. The intervention group required significantly less oral morphine equivalents on average compared to controls (0.14 vs 0.30 mg/kg; P < .001) without a significant change in length of stay or pain scores (Lee et al, 2020).…”
Section: Multimodal Analgesiamentioning
confidence: 91%
“…Multimodal therapies have been used to successfully decrease opioid use in pediatric patients after cleft surgeries, ideally allowing patients to be more awake with better airway control postoperatively. Important components of opioid reduction initiatives include provider and patient education, the utilization of nonopioid medications and nonpharmacologic pain control methods, and the standardization of a pain control protocol (Lee et al, 2020). Lee and colleagues advocated for decreasing morphine use after pediatric cleft surgery by strict adherence to a standardized order set and administration of intraoperative nerve blocks.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has demonstrated that regional anesthesia via ultrasound-guided maxillary nerve blockade reduces cumulative opiate consumption over the first 48 hours postoperatively (Mesnil et al, 2010; Chiono et al, 2014). Attempts to standardize postoperative care for patients with clefts have also been associated with reduced postoperative opioid consumption (Lee et al, 2020; Moffitt et al, 2021). Despite these findings, significant variability in analgesic approach continues to exist among pediatric centers.…”
Section: Introductionmentioning
confidence: 99%